Apolipoprotein E genotyping variations and their influence on cognitive outcome among idiopathic generalized epileptic patients - Nancy El-Salhy; Noura R. Eissa; Salma Ragab; Gamil M. Abd-Allah; Sara M. Sayed (Journal of the Arab Society for Medical Research)
Background/aim Epilepsy is a brain disorder affecting individuals of all ages. It is one of the most common neurological disorders, affecting about 50 million people globally. The study objective was to study the different genotypes of Apolipoprotein E (APOE) gene among adult idiopathic generalized epileptic patients and to assess their influence on cognitive functions of those patients. Patients and methods Forty adult patients with idiopathic generalized epilepsy (IGE) and 20 healthy controls were enrolled in this study from Kafrelsheikh Governorate, Egypt. Patients were recruited from the Neurology Department at Kafrelsheikh University Hospital. Neuropsychological evaluation was conducted to all participants. Genotyping of the APOE gene polymorphisms (rs429358 and rs7412) was then carried out using both restriction fragments length polymorphism and Sanger sequencing to evaluate the correlation between the genotype and cognitive functions of patients with IGE. Results Most of the patients and controls showed the wild type genotype ε3/ε3 of both polymorphisms of APOE gene; rs429358 and rs7412. Only six patients and one control had different genotypes other than the wild type. The study showed that a highly significant association (P<0.001) between IGE and cognitive impairment especially attention, memory, and fluency. Meanwhile, no statistically significant differences were found in distribution of Addenbrooke score and parameters according to APOE genotype distribution in patients’ group, while in controls there was no significant difference in distribution of attention and visuospatial processing parameters according to genotype distribution. Yet, there was a significant increase in Addenbrooke, memory, fluency, and language processing in ε3/ε3 genotype compared to ε3/ε4 genotype, (P=0.000, 0.007, 0.016, and 0.000, respectively). Conclusion This study supports the evidence of a distinct cognitive profile in patients with epilepsy regardless the APOE gene genotype.